Safety and efficacy of B-cell therapy in older people with multiple sclerosis - Montague, Turlough; Kang, Yuuki; Thomas, Karen; Burke Simpson, Nicole; Miller, Celia; Chatterton, Sophie; Fontes Villalba, Ariadna; Parratt, John (Frontiers in Immunology, 2026)
BackgroundThe MS population is aging, with nearly one-third now over 55 years. This group is underrepresented in trials and less often prescribed high-efficacy therapy (HET). Although phase III studies of ocrelizumab and ofatumumab confirmed efficacy in younger patients, the risk–benefit profile in older people with MS (opwMS) is less established given reduced relapse activity and higher risks of infection and malignancy.MethodsWe retrospectively reviewed opwMS (≥ 55 years) treated with ocrelizumab or ofatumumab at a tertiary centre, evaluating clinical outcomes, MRI activity, and adverse events.ResultsAmong 140 patients (67% (94) female, mean age 63), median disease duration was 16 years and B-cell therapy duration 44 months; 91% (127) had prior DMT exposure. During treatment, 77.9% (109) achieved NEDA-3, EDSS remained stable (3.38 to 3.44, p=0.67), and PIRA was reduced by 15%. Adverse events occurred in 50.7% (71%), leading to discontinuation in 10.7% (15). Immunoglobulin levels fell significantly (IgM, IgA, and IgG). In 47 patients ≥ 65 years, adverse event rates were similar, 69.6% (33) achieved NEDA-3, but EDSS increased (p=0.034).ConclusionOver 44 months, B-cell therapy in opwMS (mean age 63) showed safety and efficacy comparable with younger cohorts, although immunoglobulin decline and discontinuation due to adverse effects highlight the need for monitoring.